Wetting of monocrystalline silicon (100) surface by Sn-xAl (x = 0, 2.4 and 50 at.%) alloys and Al at 900 °C. (July 2020) - Lin, Qiaoli; Wang, Jianbin; Sui, Ran; Liu, Lu; Li, Hui
Abstract: The wetting of monocrystalline Si by molten Sn- x Al ( x = 0, 2.4 and 50 at.%) and pure Al was studied by using the modified sessile drop method at 900 °C under a high vacuum. The results showed that the segregation of Al at the solid/liquid interface intensified the dissolution of Si substrate in the Sn- x Al/Si system. In the Al/Si system, the formation of crater has certain hindrance to the spreading, and it is related to the Marangoni convection, which was caused by solute concentration gradient in the inner of drop. The effect of dissolution on wetting should consider the dissolution induced the evolution of interfacial morphology, and the dissolution only in the specific range of degrees that can act as a driving force for spreading. Generally, the spreading in this study were limited by the viscous dissipation. In Sn- x Al/Si system, the spreading was first controlled by the diffusion of Al from inner drop to the triple line, and then limited by the viscous dissipation. Highlights: Dissolution acted as driving force for spreading only in the specific range of degrees. Marangoni convection caused the formation of dissolutive crater. The scale-law indicates the spreading dynamics satisfy hydrodynamic model.